Metode Zikir Waktu Pelaksanaan Suluk Tarekat Naqsyabandiyah di Surau Tarbiyah Tangah Sawah Kota Bukittinggi - Hasibuan, Zakiah (Darul Yasin Al Sys, 2023)
The background to this title is due to the active dhikr carried out by the congregation of the Naqsyabandiyah Tarekat at Surau Tarbiyah Tengah Sawah, Bukittinggi City, which can increase the value of worship and istiqomah in carrying out Allah SWT's commands, namely dhikr, so the author also wants to know what the method of dhikr is. The problem formulation of this research is the method of remembrance during the implementation of Suluk Tarekat Naqsyabandiyah at Surau Tarbiyah Tengah Sawah, Bukittinggi City. This research aims to describe the method of remembrance during the implementation of Suluk Tarekat Naqsyabandiyah at Surau Tarbiyah Tengah Sawah, Bukittinggi City. This research is qualitative research, namely field research using observation, interviews and documentation methods. The data sources in this research are the tarekat teachers or so-called musryids of the Tarekat Naqsyabandiyah at Surau Tarbiyah Tengah Sawah, Bukittinggi City and also the congregants of the Suluk Tarekat Naqsyabandiyah at Surau Tarbiyah Tengah Sawah City. Bukittinggi. From the results of the research, it can be concluded that the method or way of praying for the congregation of the Naqsyabandiyah Tarekat at Surau Tarbiyah Tengah Sawah is carried out in 2 places in the mosquito net and in the middle of the suluk room which was deliberately left empty for congregational prayers of the suluk and bertawajuh congregation. There are two methods of remembrance, namely bertawajuh and suluk, tawajuh can be carried out in congregation in a mosque or surau led by a teacher or murshid, while the suluk is done individually in a designated place and guided by the murshid for the Naqsyabandiyah congregation at Surau Tarbiyah In the middle of the rice fields, they cover them in white mosquito nets measuring 2x1 m which are collected in one room. Tawajuh time after every morning, noon and evening prayers with the aim of always getting used to remembering Allah SWT for a long time. The remembrance of the Tarekat Naqshbandiyah Surau Tarbiyah Tengah Sawah is divided into two, namely verbal (jahar) and qolbu remembrance (pak, khafi) , the difference between the two is that oral dhikr is only on the tongue and the reading is only